2008
DOI: 10.1007/s00268-008-9588-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of CT and Ultrasonography for Evaluating Metastatic Cervical Lymph Nodes in Patients with Thyroid Cancer

Abstract: Despite of very high accuracy of USG by per patient analysis, the superior sensitivity of CT on the per level analysis may enable CT to play a complementary role for determining the surgical extent in selected patients with thyroid cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
156
7
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(184 citation statements)
references
References 49 publications
(50 reference statements)
9
156
7
1
Order By: Relevance
“…In contradistinction to other studies, we deliberately neglected all ultrasound imaging criteria for identifying nodal metastases aiming to increase the sensitivity, and any lymph node detected in the central compartment was considered positive. The specificity of US in our study was 75%, which is still higher than that reported in some previous studies [20].…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In contradistinction to other studies, we deliberately neglected all ultrasound imaging criteria for identifying nodal metastases aiming to increase the sensitivity, and any lymph node detected in the central compartment was considered positive. The specificity of US in our study was 75%, which is still higher than that reported in some previous studies [20].…”
Section: Discussioncontrasting
confidence: 54%
“…Firstly, the technical difficulty; where metastatic nodes may be masked by the enlarged thyroid gland and the multifocal nodules and the presence of many surrounding structures with poor acoustic transmission [19,20,22], figure 3. Secondly, it should be noted that the experience of radiologists in US imaging of the central neck compartment is lower than that in the lateral neck.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are no published reports that address the diagnostic value of US and CT for the evaluation of lymph node metastasis in PTMC. Previous studies (27,28) reported that for US, the sensitivity, specificity, accuracy, PPV and NPV at the lateral neck level of patients with PTC were 64 ∼65%, 82∼92%, 71∼82%, 83∼86%, and 59∼82%, respectively, while these diagnostic values for CT were 74 ∼78%, 78∼95%, 78∼87%, 86∼89%, and 68∼86%. Kim et al (27) reported a slight difference between the diagnostic accuracies of US and CT and that combined US and CT is superior to US alone in the detection of lymph node metastasis from PTC.…”
Section: Methodsmentioning
confidence: 99%
“…Kim et al (27) reported a slight difference between the diagnostic accuracies of US and CT and that combined US and CT is superior to US alone in the detection of lymph node metastasis from PTC. Ahn et al (28) reported that the sensitivity of CT was significantly higher than that of US for whole neck levels. We found that the sensitivity, specificity and accuracy for US and CT at the lateral neck level of patients with PTMC were comparable to that of the …”
Section: Methodsmentioning
confidence: 99%
“…The sensitivity (27.3-55%) and specificity (69-90.0%) of preoperative US within the central compartment are lower than those (sensitivity 65-90.3%, specificity 82-94.8%) of the lateral compartment. [31][32][33][34] Recently several investigators have reported that preoperative US with CT had superior diagnostic performances to US alone, although the routine preoperative usage of CT is not recommended by the American Thyroid Association (ATA) guidelines under revision. 33,35,36) However, US and CT together were still not sufficiently sensitive to detect small lymph node metastases in the central neck.…”
Section: Presentation Of Nodal Metastasesmentioning
confidence: 99%